Carbazole-grafted silicone hydrogel with a high refractive index for intraocular lens. Issue 89 (27th September 2015) - Xu, Jinku; Zhu, Weiyue; Jiang, Lijuan; Xu, Jing; Zhang, Yongchun; Cui, Yuezhi
<x xml:space="preserve">Abstract</x> The refractive index (RI) is an important parameter for intraocular lens biomaterials.